Game design for teens - Pardew, Les (Thomson Course Technology, 2004)
Game Design for Teens covers the basics for developing a game idea and successfully converting that idea into a complete game. A natural addition to the "for Teens" line of books, it is a true beginner's guide to the game design process and deals specifically with creating a game design document. It will help the reader create a quality game design document appropriate for submission to a publisher, developer, or college professor. It explores the components of a game design document, how to create each component, who creates each portion, and why each is important. This book also examines game design theory as it applies to different game genres